Genetic diversity of Moringa oleifera Lam. in the northeast of Colombia using RAMs markers (2018)
Moringa oleifera Lam., also known as Moringa pterygosperma Gaertn., is a fast growing tree, indigenous to Himalaya that has been used as food or as medicine, recognized for its bioactive compounds. In Colombia, moringa has been promoted primarily because of its medicinal properties. However, despite the importance of this phytogenetic resource, there are no studies on its genetic variability. In this study, we analyzed 45 accessions of moringa from four departments in the northeast of Colombia. The DICE and Nei-Li coefficients, at a level of similarity of 0.75, differentiated the population into four genetic groups. The expected heterozygosity was 0.13 for the oligo CT and 0.29 for the oligos CGA and GT. The percentage of polymorphic loci ranged from 31 to 100% for the primers CT and CA, respectively. With the UPGMA grouping, we revealed that the Moringa accessions from Villa del Rosario in Norte de Santander are genetically isolated. The genetic diversity of the studied Moringa accessions was low. This knowledge on the genetic variability of moringa provides a new contribution to Colombian growers that can be used in future breeding programs.